Simultaneous Relationship Between Ownership Structure, Corporate Governance, and Firm Value in Indonesia - Suk, Kim Sung (The South East Asian Journal of Management, 2008)
The primary objective of this study is to test the simultaneous relationship between the firm value, the corporate governance practice, and the ownership structure on a sample of 114 companies quoted in the Jakarta Stoke Exchange (JSX). The study finds that the corporate governance practice fails to affect the firm value, but the firm value is a positive predictor of corporate governance practice. Further, the influence of corporate governance practice on the firm value becomes less when the wedge of the firm becomes higher. The ownership structure and the firm value have no systematic relationship. Controlling shareholders and foreign blockholders that presumably are Indonesia blockholders (FBIB) do not extract private benefits for themselves or do not exproproate the wealth of the minority shareholders. But, the percentage of ownership by FBIB has negative influence on the corporate governance practice.